Coloniality in the Maya Lowlands : Archaeological Perspectives - Douglass, John G., 1968-; Fryer, Tiffany C.; Diserens Morgan, Kasey (Book collections on Project MUSE., 2022)
"This volume offers a materialist perspective on coloniality and takes a hemispheric approach to the historical and material analysis of colonialism. Bringing together nineteen archaeologists and anthropologists working in southeastern Mexico, Belize, Guatemala, and Honduras, the contributors grapple with the material realities of coloniality at a regional level." --